Vitamin D ameliorates stress ligand expression elicited by free fatty acids in the hepatic stellate cell line LX-2 - Şeyda SEYDEL; Anja BEILFUSS; Alişan KAHRAMAN; Kıymet AKSOY; Guido GERKEN; Hikmet AKKIZ; Ali CANBAY (Turkish Journal of Gastroenterology, 2019)
-